2013
DOI: 10.1017/s0020818312000379
|View full text |Cite
|
Sign up to set email alerts
|

Unthinkable and Tragic: The Psychology of Weapons Taboos in War

Abstract: Discussions of weapons taboos have failed to take into account the possibility that prescriptive international and national norms of behavior may come into conflict. Using psychological studies of trade-offs and protected values as a guide, this article argues that when these conflicts exist, the taboos' individual-level constraining effects can be vitiated. An analysis of General George Marshall's proposal to use chemical weapons against the Japanese in 1945 demonstrates that normative conflict can produce a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…The use of nuclear weapons has both potential advantages and disadvantages that must be weighed against one another but which are understood and valued differently by every person. Dolan (2013) has demonstrated such a trade-off consideration in a qualitative analysis of American elites. We aim to identify the underlying moral structure of this calculation.…”
Section: Building a Moral Utilitarian Argument With Multiple Moral Inmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of nuclear weapons has both potential advantages and disadvantages that must be weighed against one another but which are understood and valued differently by every person. Dolan (2013) has demonstrated such a trade-off consideration in a qualitative analysis of American elites. We aim to identify the underlying moral structure of this calculation.…”
Section: Building a Moral Utilitarian Argument With Multiple Moral Inmentioning
confidence: 99%
“…However, studies have shown that public opinion can shape the menu of acceptable options even in the most existential crises (McKeown 2000) and that the public is less dependent on elites for their attitudes than has been posited by the literature on elite cues (Berinsky 2009). Moreover, Dolan (2013) shows that elites face the same moral trade-offs.…”
Section: Conclusion: Situating Individual-level Findings In the Broadmentioning
confidence: 99%
“…Crawford (:550) highlights the importance of emotions in affecting material decisions that revolve around interests and positions: “[t]he perception and creation of interests is an emotional process as well as one rooted in a material reality or drive for power.” Kertzer and McGraw () make a similar point on the ideational/material distinction, demonstrating that fear plays a significant role in realist theory writ large , a paradigm traditionally dominated by materialist perspectives, as well as in the minds of ordinary individuals. Their model provides significant benefits as the literature includes emotional variables in a wide swath of areas of IR, from nuclear politics (2012), weapons taboos (Dolan ), sincerity assessment (Hall and Yarhi‐Milo ; Holmes ), and generalized trust (Rathbun ), to funding for homeland security (Mueller and Stewart ). Sasley's (:688, 690) application of the affect heuristic by decision makers shows how leaders make necessary simplifications, including the tagging of stimuli with “affective label[s],” (Sasley :690), in making decisions.…”
Section: Approaches To Emotions In Ir and Foreign Policy Analysismentioning
confidence: 99%
“…Important scholarly and policy work on 'weapons taboos' -moral opprobriums restricting or prohibiting the use or development of certain weapons -demonstrates that some very efficient weapons (e.g. chemical weapons) can be removed from the assumed inventory of war (Dolan, 2013;Price, 1997;Tannenwald, 2008). The tenor of this work is to focus on those weapons that are rendered illegitimate, even inhumane, in the practice of warfare.…”
Section: Becoming a Weaponmentioning
confidence: 99%